3′, 4′, 7-Trihydroxyflavone prevents apoptotic cell death in neuronal cells from hydrogen peroxide-induced oxidative stress. (June 2015) - Kwon, Seung-Hwan; Hong, Sa-Ik; Ma, Shi-Xun; Lee, Seok-Yong; Jang, Choon-Gon
Highlights: THF significantly reduced H2 O2 -induced cell death and cytotoxicity. THF inhibited H2 O2 -induced mitochondrial membrane dysfunction. THF suppressed H2 O2 -induced phosphorylation of JNK, p38, and Akt. THF inhibited activation of NF-κB translocation induced by H2 O2 . Graphical Abstract: Abstract: In this study, we investigated the mechanisms of 3′, 4′, 7-trihydroxyflavone (THF) protection of neuronal cells from neuronal cell death induced by the oxidative stress-related neurotoxin hydrogen peroxide (H2 O2 ). Pretreatment with THF significantly elevated cell viability, reduced H2 O2 -induced lactate dehydrogenase (LDH) release, reactive oxygen species (ROS) production, glutathione (GSH) content, superoxide dismutase (SOD) activity, catalase (CAT) activity, and mitochondria membrane potential (MMP) loss. Western blot data demonstrated that THF inhibited the H2 O2 -induced up- or down-regulation of cleaved caspase-3, cleaved caspase-9, cleaved poly-ADP-ribose polymerase (PARP), Bax, Bcl-2, and Bcl-xL, and attenuated the H2 O2 -induced release of cytochrome c from the mitochondria to the cytosol. In addition, pretreatment with THF attenuated H2 O2 -induced rapid and significant phosphorylation of c-Jun N-terminal kinase (JNK), p38 mitogen-activated protein kinase (MAPK), and phosphatidylinositol 3-kinases (PI3K)/Akt. THF also inhibited nuclear factor-κB (NF-κB) translocation to the nucleus induced by H2 O2, down-stream of H2 O2 -induced phosphorylation of MAPKs and PI3K/Akt. These data provide the first evidence that THF protects neuronal cells against H2 O2 -induced oxidative stress, possibly through ROS reduction, mitochondria protection, and NF-κB modulation via MAPKs and PI3K/Akt pathways. The neuroprotective effects of THF make it a promising candidate as a therapeutic agent for neurodegenerative diseases.